2022
DOI: 10.1007/s11135-022-01518-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the prestige of administrative courts

Abstract: This article examines the citation practices of the provincial administrative courts in Poland in a sample of judgments issued in the years 2009–2016. The analysis strives to assess the factors affecting the use of other court citations and the prestige of provincial courts manifested in the higher citations of their verdicts. The methods used involve logistic and zero-inflated negative binomial regressions on the set of factors relating to court circuit characteristics, the performance of courts, the features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
2
0
2
Order By: Relevance
“…Thus, academic freedom can be derived from freedom of opinion and expression and from the right to education. 30 Similarly, we can observe this in Article 10 of the European Convention of Human Rights, in Article 19 of the International Covenant on Civil and Political Rights and in Article 13 of the International Covenant on Economic, Social and Cultural Rights.…”
Section: Academic Freedom As a Fundamental Freedommentioning
confidence: 69%
“…Thus, academic freedom can be derived from freedom of opinion and expression and from the right to education. 30 Similarly, we can observe this in Article 10 of the European Convention of Human Rights, in Article 19 of the International Covenant on Civil and Political Rights and in Article 13 of the International Covenant on Economic, Social and Cultural Rights.…”
Section: Academic Freedom As a Fundamental Freedommentioning
confidence: 69%
“…The growing attention on the functioning of the judicial system has also stimulated several studies on different aspects of judgment quality, which should be verified by reducing the court delay to avoid the higher speed potentially being traded off for lower quality. Stachowiak-Kudła and Kudła (2023) noted that judicial quality included independence, accountability and effectiveness of each court, and sometimes citation counts were used in literature as proxies for judicial quality. Mocan et al (2020) suggested several indicators of judicial quality for ninety-five European countries to evaluate the impact on propensity for dishonest behaviour.…”
Section: The Relationship Between Quality Indicators and Judicial Eff...mentioning
confidence: 99%
“…[Z] autonomią dydaktyczno-naukową szkoły wyższej wiąże się prawo do: samodzielnego określania misji uczelni; prowadzenia badań naukowych (wolność nauki); tworzenia kierunków studiów; wyboru formy studiów i określania ich regulaminu; kształcenia na podstawie uchwalonych przez rady podstawowych jednostek organizacyjnych uczelni planów studiów i programów kształcenia (wolność nauczania); określania szczegółowych zasad i trybu przyjmowania na studia; wydawania państwowych dyplomów ukończenia studiów; nadawania stopni naukowych doktora i doktora habilitowanego oraz występowania o nadanie tytułu naukowego profesora 51 .…”
unclassified
“…Autonomia dydaktyczno-naukowa to między innymi wolność prowadzenia badań naukowych, samodzielne określanie misji uczelni czy tworzenie kierunków studiów 52 . W zakresie autonomii finansowej szkoły wyższe mogą "podejmować działalność gospodarczą, dysponować majątkiem, zaciągać zobowiązania oraz pobierać opłaty za usługi edukacyjne" 53 .…”
unclassified